Timo J. Partanen (MSc, MPH, PhD) March 13, 1938–May 1, 2015 Defender of the invisibles Promotor of improved labor conditions in Central America and East Africa Visiting professor, 2004–2009 Central American Institute for Studies on Toxic Substances (IRET), Pan-American Health Organization (PAHO) Collaborating Center, Universidad Nacional, Heredia, Costa Rica (Scandinavian Journal of Work, Environment & Health, 2015)
On 1 May, the day designated as the International Workers Day, Timo Partanen departed from this life. This loss is a great one for the Universidad Nacional (UNA) in Costa Rica and particularly for the Central American Program for Health, Work and Environment (SALTRA) at the Central American Institute for Studies on Toxic Substances (IRET). Timo was a constant source of wisdom and inspiration for researchers, extension workers, and professors from many countries and will be remembered for his analytical capability as well as his drive to address the urgent needs of populations who have been traditionally overlooked in the occupational health and labor agendas in the region: informal workers in urban and agricultural settings, construction workers, health workers, and many more. Those of us fortunate enough to work with him were privy to valuable lessons that developed in the spaces we shared: humility; the ability to construct and deconstruct horizontally; an integrated and ample perspective allowing for the identification of preventative solutions; the importance of creating the conditions necessary for wellbeing; and a focus on health promotion. We will remember Timo for his continually happy disposition along with his practical, yet disciplined actions to create positive change. For many years, he refused to give into the disease that threatened to stop his research and during this period, he used his energies to work on many urgent health issues including research on occupational cancer, childhood cancer, and neurogedenerative diseases. Together with his partner, Catharina (Ineke) Wesseling, Timo had an enormous positive impact on the Central American region in its fight for improved working conditions and employment of workers and communities. As stated by José Martí: “Death is not true when the work of life has been fulfilled well.” Programa Salud Trabajo y Ambiente en América Central (SALTRA)
Keywords: obituary